Potential Host Range of the Larval Endoparasitoid Cotesia vestalis (=plutellae) (Hymenoptera: Braconidae). (23rd June 2017) - Hiroyoshi, Satoshi; Harvey, Jeffrey A; Nakamatsu, Yutaka; Nemoto, Hisashi; Mitsuhashi, Jun; Mitsunaga, Takayuki; Tanaka, Toshiharu
Many parasitoid wasps are highly specialized in nature, attacking only one or a few species of hosts. Host range is often determined by a range of biological and ecological characteristics of the host including diet, growth potential, immunity, and phylogeny. The solitary koinobiont endoparasitoid wasp, Cotesia vestalis, mainly parasitizes diamondback moth (DBM) larvae in the field, although it has been reported that to possess a relatively wide lepidopteran host range. To better understand the biology of C vestalis as a potential biological control of hosts other than the DBM, it is necessary to determine suitability for potential hosts. In this study, the potential host range of the wasp and its developmental capacity in each host larva were examined under laboratory conditions using 27 lepidopteran species from 10 families. The wasp was able to parasitize 15 of the 27 species successfully. Some host species were not able to exclude C vestalis via their internal physiological defenses. When parasitization was unsuccessful, most hosts killed the parasitoid at the egg stage or early first-instar stage using encapsulation, but some host species disturbed the development of the parasitoid at various stages. No phylogenetic relationships were found among suitable and unsuitable hosts, revealing that host range in some endoparasitoids is not constrained by relatedness among hosts based on immunity.